Effects of Mobile Phone Induced Electromagnetic Field on Height of Follicular Cells in Thyroid Gland of Mice - Farheen Shaukat, Khadija Qamar, Shadab Ahmed Butt (Journal of Rawalpindi Medical College, 2011)
Background: To study the effects of electromagnetic radiations generated by mobile phone on height of follicular cells in thyroid gland of mice. Methods: In this experimental study, 20 adult BALB/C male mice were divided randomly into two groups, comprising of 10 animals in each group. Group A was kept under same experimental conditions without mobile phone exposure, group B received 50 missed calls /day, from mobile phone set. Thyroid gland was removed 24 hours after the last experimental day. These were then processed and analyzed. Results: There was significant difference in mean height of follicular epithelium in thyroid gland of control and experimental group. Conclusion: Long term exposure to electro magnetic fields (EMFs) causes increase in size of follicular cells of thyroid gland of mice.